PENGUKURAN KINERJA GREEN SUPPLY CHAIN MANAGEMENT PADA INDUSTRI PENYAMAKAN KULIT YOGYAKARTA - Purnomo, Hari; Kisanjani, Alex; Kurnia, Wahyu Ismail; Suwarto, Sigit (Jurnal Ilmiah Teknik Industri, 2019)
The application of GSCM (Green Supply Chain Management) practice in the leather tanning industry in Yogyakarta is still relatively difficult because the industry prefers manufacturing systems that can accelerate profit uplift without considering environmental quality. Therefore, this research attempts to measure GSCM performance applied in the leather tanning industry, particularly at PT. Asa Yogyakarta. The method used in this research is Green SCOR (Green Supply Chain Operations Reference) and AHP (Analytical Hierarchy Process). Data collection in this research was by identifying the company's GSCM activities, then compiling performance indicators that refer to the green SCOR method. Weighting performance indicators are conducted to determine the importance of each performance indicator by using the AHP method. The results of this research indicate that the application of GSCM is quite good with the average value of the total GSCM performance >90, despite several improvements that are necessary to enhance the performance.